2016
DOI: 10.1007/s10549-016-3750-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II trial of the safety and clinical activity of a HER2-protein based immunotherapeutic for treating women with HER2-positive metastatic breast cancer

Abstract: The objectives of this phase I/II study (NCT00140738) were to evaluate the safety and clinical activity of a cancer immunotherapeutic agent (recombinant HER2 protein (dHER2) and the immunostimulant AS15) in patients with HER2-overexpressing metastatic breast cancer (MBC). Forty HER2-positive MBC patients received up to 18 doses (12q2w, 6q3w) of dHER2 immunotherapeutic, as first- or second-line therapy following response to trastuzumab-based treatment as maintenance. Toxicity was graded by the Common Terminolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…This finding was confirmed with larger patient sample in the recently finished phase III clinical trial (manuscript in preparation). Another exploratory study using a HER2 protein-based vaccine in HER2+ metastatic breast cancer patients found that a longer progression-free-survival time was observed for patients with high anti-HER2-ECD antibodies concentrations compared to low antibody response (Curigliano et al, 2016). In addition, in a phase III clinical trial in which Sipuleucel T was administered to CRPC patients, IgG response to PSAs was associated with improved OS in vaccinated patients (GuhaThakurta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed with larger patient sample in the recently finished phase III clinical trial (manuscript in preparation). Another exploratory study using a HER2 protein-based vaccine in HER2+ metastatic breast cancer patients found that a longer progression-free-survival time was observed for patients with high anti-HER2-ECD antibodies concentrations compared to low antibody response (Curigliano et al, 2016). In addition, in a phase III clinical trial in which Sipuleucel T was administered to CRPC patients, IgG response to PSAs was associated with improved OS in vaccinated patients (GuhaThakurta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The response increased with increasing doses and frequency of vaccination. In another recent Phase I/II study with recombinant dHER2 plus AS15 in patients with HER2‐overexpressing metastatic breast cancer as first‐ or second‐line therapy after response to trastuzumab‐based treatment as maintenance, 1 of 40 patients achieved complete remission lasting for 11 months, and 1 of 40 patients had a partial response for 3.5 months according to RECIST . Humoral and cellular immunity to the dHER2 antigen was demonstrated, and 10 of 40 patients achieved prolonged stable disease.…”
Section: Her2 Hybrid Ae37 Peptidementioning
confidence: 99%
“…Humoral and cellular immunity to the dHER2 antigen was demonstrated, and 10 of 40 patients achieved prolonged stable disease. The vaccine was well tolerated with minimal adverse reactions . The trial also evaluated dHER2 in combination with lapatinib (NCT00952692).…”
Section: Her2 Hybrid Ae37 Peptidementioning
confidence: 99%
“…Current advances include the development of immunotherapeutic vaccines, such as the dHer2 vaccine, which is aimed at inducing comprehensive anti‐Her2 immunity and is in clinical testing for breast cancer treatment. It has reached phase I/II trials and was shown to be safe and well tolerated …”
Section: Kinases As Targets Of Cancer Therapiesmentioning
confidence: 99%